Lestvica doseganja ciljev za vrednotenje napredka v obravnavi otrok s posebnimi potrebami - Merhar, Anita (Rehabilitacija (Ljubljana), 2016)
Background: Occupational therapists have a range of evaluation instruments at their disposal, which they use to evaluate the recovery progress of a patient and thus the effectiveness of the occupational therapy intervention. Often, however, these evaluation instruments are not sensitive enough to detect small changes in children with functional disabilities. In this study we wanted to check the complementarity and coherence of two evaluation instruments aimed at evaluating the progress of children with special needs, the Goal Attainment Scaling (GAS) and the Paediatric Evaluation of Disability Inventory (PEDI), both aimed at evaluating the progress of children with special needs. We tried to establish whether or not GAS can detect small improvements in the performance of the child % improvements that other instruments cannot detect. We hypothesised the following outcomes: that GAS will detect progress to a greater extent than PEDI; that GAS will also detect lesser progress in compacter and shorter therapeutic periods of time; that age will not affect progression. The progress, however, will be lesser in children with a severe disability or a higher degree of disability (i.e. with Cerebral Paralysis).
Keywords: child; children with disabilities; delovna terapija; Disability Evaluation; Disabled Children; evaluation; goal attainment scaling; lestvica doseganja ciljev; occupational therapy; ocenjevanje; Ocupational Therapy; otroci; prizadetost; rehabilitacija; rehabilitation; vocational rehabilitation